Optimization of a tracking-based approach for calculating energy expenditure and aerobic-anaerobic supplies during intermittent running: improved simulation of oxygen uptake within the metabolic power model - Brochhagen, J.; Schnack, T.; Baumgart, C.; Hoppe, M. W. (Sensors, 2025)
What are the main findings?